Tauroursodeoxycholic acid prevents Burkholderia pseudomallei-induced endoplasmic reticulum stress and is protective during melioidosis in mice - Siqi Yuan; Yao Fang; Mengling Tang; Zhiqiang Hu; Chenglong Rao; Jiangao Chen; Yupei Xia; Meijuan Zhang; Jingmin Yan; Bin Tang; Xiaoyi He; Jianping Xie; et al. (BMC Microbiology, 2021)
Abstract Background Burkholderia pseudomallei, a facultative intracellular bacterium, is the aetiological agent of melioidosis that is responsible for up to 40% sepsis-related mortality in epidemic areas. However, no effective vaccine is available currently, and the drug resistance is also a major problem in the treatment of melioidosis. Therefore, finding new clinical treatment strategies in melioidosis is extremely urgent. Results We demonstrated that tauroursodeoxycholic acid (TUDCA), a clinically available endoplasmic reticulum (ER) stress inhibitor, can promote B. pseudomallei clearance both in vivo and in vitro. In this study, we investigated the effects of TUDCA on the survival of melioidosis mice, and found that treatment with TUDCA significantly decreased intracellular survival of B. pseudomallei. Mechanistically, we found that B. pseudomallei induced apoptosis and activated IRE1 and PERK signaling ways of ER stress in RAW264.7 macrophages. TUDCA treatment could reduce B. pseudomallei-induced ER stress in vitro, and TUDCA is protective in vivo. Conclusion Taken together, our study has demonstrated that B. pseudomallei infection results in ER stress-induced apoptosis, and TUDCA enhances the clearance of B. pseudomallei by inhibiting ER stress-induced apoptosis both in vivo and in vitro, suggesting that TUDCA could be used as a potentially alternative treatment for melioidosis.